Brain Delivery of Single-Domain Antibodies: A Focus on VHH and VNAR - Elodie Pothin; Dominique Lesuisse; Pierre Lafaye (MDPI AG, 2020)
Passive immunotherapy, i.e., treatment with therapeutic antibodies, has been increasingly used over the last decade in several diseases such as cancers or inflammation. However, these proteins have some limitations that single-domain antibodies could potentially solve. One of the main issues of conventional antibodies is their limited brain penetration because of the blood-brain barrier (BBB). In this review, we aim at exploring the different options single-domain antibodies (sDAbs) such as variable domain of heavy-chain antibodies (VHHs) and variable new antigen receptors (VNARs) have already taken to reach the brain allowing them to be used as therapeutic, diagnosis or transporter tools.